2022
DOI: 10.4103/jfmpc.jfmpc_2014_21
|View full text |Cite
|
Sign up to set email alerts
|

Influence of laboratory biomarkers on inflammatory indices for assessing severity progression in COVID-19 cases

Abstract: Background and Objective: This study explored the role of various laboratory biomarkers on inflammatory indices for predicting disease progression toward severity in COVID-19 patients. Methods: This retrospective study was conducted on 1233 adults confirmed for COVID-19. The participants were grouped undermild, moderate, and severe grade disease. Serum bio-inflammatory index (SBII) and systemic inflammatory index (SII) were calculated and correlated with disease severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The study design was prospective in three studies ( 50 , 67 , 68 ), unclear in one ( 66 ), and retrospective in the remaining 36 ( 21 , 36 49 , 51 65 , 69 74 ). The clinical endpoints included mortality in 19 studies ( 36 , 37 , 39 , 41 , 43 , 45 , 48 , 49 , 51 , 52 , 55 , 56 , 58 , 60 , 61 , 65 , 66 , 68 , 73 ), and measures of severe disease as follows: disease severity based on existing guidelines in eight ( 42 , 44 , 63 , 64 , 67 , 70 , 72 , 74 ), transfer to the intensive care unit (ICU) in eight ( 38 , 40 , 45 , 50 , 53 , 62 , 68 , 69 ), invasive mechanical ventilation in two ( 46 , 52 ), disease progression in two ( 57 , 71 ), prolonged hospital stay in one ( 21 ), intubation in one ( 37 ), deep vein thrombosis in one ( 54 ), acute pulmonary embolism in one ( 54 ), and acute limb ischemia in one ( 39 ). All studies reported the SII on hospital admission.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study design was prospective in three studies ( 50 , 67 , 68 ), unclear in one ( 66 ), and retrospective in the remaining 36 ( 21 , 36 49 , 51 65 , 69 74 ). The clinical endpoints included mortality in 19 studies ( 36 , 37 , 39 , 41 , 43 , 45 , 48 , 49 , 51 , 52 , 55 , 56 , 58 , 60 , 61 , 65 , 66 , 68 , 73 ), and measures of severe disease as follows: disease severity based on existing guidelines in eight ( 42 , 44 , 63 , 64 , 67 , 70 , 72 , 74 ), transfer to the intensive care unit (ICU) in eight ( 38 , 40 , 45 , 50 , 53 , 62 , 68 , 69 ), invasive mechanical ventilation in two ( 46 , 52 ), disease progression in two ( 57 , 71 ), prolonged hospital stay in one ( 21 ), intubation in one ( 37 ), deep vein thrombosis in one ( 54 ), acute pulmonary embolism in one ( 54 ), and acute limb ischemia in one ( 39 ). All studies reported the SII on hospital admission.…”
Section: Resultsmentioning
confidence: 99%
“…The risk of bias was low in 29 studies ( 21 , 36 , 37 , 39 41 , 43 45 , 47 , 49 , 51 53 , 55 61 , 64 , 65 , 67 , 69 , 71 74 ) and high in the remaining ten ( 38 , 42 , 46 , 48 , 50 , 62 , 63 , 66 , 68 , 70 ) ( Supplementary Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations